Answer:
[tex]x = -3[/tex]
Step-by-step explanation:
To rewrite the expression [tex]3^{5x} = 27^{2x+1}[/tex] using properties of logarithms, let's start by expressing both sides with the same base:
Recall that [tex]27 = 3^3[/tex], so [tex]27^{2x+1} = (3^3)^{2x+1} = 3^{3(2x+1)}[/tex].
So, we rewrite the equation as:
[tex]3^{5x} = 3^{3(2x+1)}[/tex]
Now, using the property of logarithms that states [tex]a^b = a^c[/tex] if and only if [tex]b = c[/tex], we can equate the exponents:
[tex]5x = 3(2x+1)[/tex]
Now, let's solve for [tex]x[/tex]:
[tex]5x = 6x + 3[/tex]
[tex]5x - 6x = 3[/tex]
[tex]-x = 3[/tex]
[tex]x = -3[/tex]
So, the value of x is [tex] -3[/tex].